2008
DOI: 10.1021/ef800265x
|View full text |Cite
|
Sign up to set email alerts
|

CO2Reforming of CH4over Co/Oxidized Diamond Catalyst

Abstract: We examined synthesis gas (H 2 and CO) production from CO 2 reforming of methane using a Co/oxidized diamond catalyst to investigate the properties of oxidized diamond as a support material and as a way to avoid carbon deposition on cobalt-loaded catalysts. Oxidized diamond showed a good catalytic performance among various support materials. No carbon deposition was observed when using the Co/oxidized diamond catalyst in CO 2 reforming of CH 4 . In addition, CH 4 conversion was maintained for 10 h during CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In this mechanism, the reaction between a molecule of methane and Ni surface (Nickel has the best conversion among other metals due to its size and high density of posi-tive charge [10] ) produced desorbed hydrogen and hydrocarbon species CHx (x = 0-4); when x=0, carbon deposits on the Ni metal surface [35]. Equations 10-14 are shown below: CH4 + 2Ni(as)  CH3Ni(as) + HNi(as) (10) CH3Ni(as) + Ni(as)  CH2NI(as) + HNi(as) (11) CH2Ni(as) + Ni(as)  CHNi(as) + HNi(as) (12) CHNi(as) + Ni(as)  CNi(as) + HNi(as) (13) 2HNi(as)  H2 + 2Ni(as) (14) (as) metal active site Nakamura et al [36] described the effects of a promoter on the catalyst during the DRM through an increase in the dispersion of Pt, Pd, and Ni. One of the effects was the activation of carbon dioxide on the support-promoter that had been mixed with the metal particle for the formation of a carbonate species.…”
Section: Effects Of Reactant Concentration On Conversionmentioning
confidence: 99%
“…In this mechanism, the reaction between a molecule of methane and Ni surface (Nickel has the best conversion among other metals due to its size and high density of posi-tive charge [10] ) produced desorbed hydrogen and hydrocarbon species CHx (x = 0-4); when x=0, carbon deposits on the Ni metal surface [35]. Equations 10-14 are shown below: CH4 + 2Ni(as)  CH3Ni(as) + HNi(as) (10) CH3Ni(as) + Ni(as)  CH2NI(as) + HNi(as) (11) CH2Ni(as) + Ni(as)  CHNi(as) + HNi(as) (12) CHNi(as) + Ni(as)  CNi(as) + HNi(as) (13) 2HNi(as)  H2 + 2Ni(as) (14) (as) metal active site Nakamura et al [36] described the effects of a promoter on the catalyst during the DRM through an increase in the dispersion of Pt, Pd, and Ni. One of the effects was the activation of carbon dioxide on the support-promoter that had been mixed with the metal particle for the formation of a carbonate species.…”
Section: Effects Of Reactant Concentration On Conversionmentioning
confidence: 99%
“…As Co loading increases, the catalytic activity of the catalyst increases until the saturation point reached. The micro-porous structure of the carbon surface is blocked when Co loading exceeds the saturation point [12][13][14][15][16][17]. It is not conducive to gas molecule adsorption and activation.…”
Section: Effects Of Impregnation Amountmentioning
confidence: 99%
“…It is Co and CoAl 2 O 4 that play a very important role in the reaction, and there are many different catalytic features between calcined at high temperature and at low temperature. In summary, Co metal has high catalytic activity, and can form moderately granular crystal after calcination [13][14][15][16][17]. However, the catalyst life is still short.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in the studies have shown that the carbon-based supports such as the activated carbon [13,14], carbon nanotubes (CNTs) [9,[15][16][17], oxidized diamond [18] and coal char [19] could prevent extensive amount of the carbon deposition from the hydrocarbons. Among them, the use of CNTs as the catalyst supports seems to be one of the most promising fields with large economic implications.…”
Section: Introductionmentioning
confidence: 99%